Examining the relationship between early childhood temperament, trauma, and post-traumatic stress disorder. (December 2021) - Wiseman, Chantelle; Croft, Jazz; Zammit, Stan
Abstract: A greater understanding of why some people are more at risk of developing PTSD is required. We examine the relationship between temperament traits in early childhood and subsequent trauma exposure and risk of PTSD. We used data on 2017 participants from the Avon Longitudinal Study of Parents and Children (ALSPAC). Temperament was measured using the Carey Infant Temperament Scale (average score from ages 6 and 24 months). This provided data on 9 individuals traits, and Easy, Medium, and Difficult temperament clusters. Trauma exposure was measured from 0 to 17 years, and PTSD at age 23 years using the PTSD Checklist for DSM-V (PCL-5). Regression models were used to estimate associations between temperament and both trauma and PTSD, and to examine mediation (of temperament to PTSD pathway) and interaction (temperament X trauma on PTSD) effects. 1178 (58.4%) individuals were exposed to a trauma in childhood and 112 (5.5%) had PTSD. Higher levels of Intensity were associated with a small increase in trauma exposure (ORadjusted 1.23, 95% CI 1.12, 1.34; p  < 0.001) and PTSD (ORadjusted 1.27, 95% CI 1.05, 1.54; p  = 0.012). Higher levels of Activity, Adaptability, Mood and Threshold temperament traits were also associated with trauma exposure. Medium (ORadjusted 1.49, 95% CI 1.21, 1.84; p  < 0.001) and Difficult (ORadjusted 1.47, 95% CI 1.18, 1.84; p  = 0.001) temperament clusters were associated with increased trauma exposure compared to an Easy cluster, but were not associated with PTSD. The relationship between trait Intensity and adult PTSD was partially mediated by childhood/adolescent trauma (Indirect ORadjusted 1.08, 95% CI 1.01, 1.16, p  = 0.024, proportion mediated 26.2%). There was some evidence that trait Intensity modified the relationship between trauma and PTSD (ORadjusted 1.66, 95% CI 1.07, 2.55, p = 0.023). PTSD in early adulthood is more common in those with intense stimuli responsiveness in childhood. Temperament traits might be useful predictors of trauma exposure and mental health outcomes and offer potential targets for supportive interventions.